化简求值:(-m^4/m^2)^2+(-2m)^3*m^2+(-m^2)^4/m^4,其中m=-1

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 13:46:25
化简求值:(-m^4/m^2)^2+(-2m)^3*m^2+(-m^2)^4/m^4,其中m=-1化简求值:(-m^4/m^2)^2+(-2m)^3*m^2+(-m^2)^4/m^4,其中m=-1化简

化简求值:(-m^4/m^2)^2+(-2m)^3*m^2+(-m^2)^4/m^4,其中m=-1
化简求值:(-m^4/m^2)^2+(-2m)^3*m^2+(-m^2)^4/m^4,其中m=-1

化简求值:(-m^4/m^2)^2+(-2m)^3*m^2+(-m^2)^4/m^4,其中m=-1
原式=:m^8/m^4-8m^3*m^2+m^8/m^4=m^4-8m^5+m^4=2m^4-8m^5=2+8=10

(-m^4/m^2)^2+(-2m)^3*m^2+(-m^2)^4/m^4
=(m²)²-8m³m²+m^8/m^4
=m^4-8m^5+m^4
=2m^4-8m^5
当m=-1时
原式=2×(-1)^4-8×(-1)^5=2+8=10